Laryngopharyngeal reflux and Helicobacter pylori - Yılmaz, Taner (Baishideng Publishing Group Inc, 2014)
Laryngopharyngeal reflux (LPR) occurs when gastric contents pass the upper esophageal sphincter, causing symptoms such as hoarseness, sore throat, coughing, excess throat mucus, and globus. The pattern of reflux is different in LPR and gastroesophageal reflux. LPR usually occurs during the daytime in the upright position whereas gastroesophageal reflux disease more often occurs in the supine position at night-time or during sleep. Ambulatory 24-h double pH-probe monitoring is the gold standard diagnostic tool for LPR. Acid suppression with proton pump inhibitor on a long-term basis is the mainstay of treatment. Helicobacter pylori (H. pylori) is found in many sites including laryngeal mucosa and interarytenoid region. In this paper, we aim to present the relationship between LPR and H. pylori and review the current literature.